Pengembangan E-Modul Interaktif Berbasis Flipbook Pada Materi Perawatan Wajah Berminyak Secara Manual di SMP Terbuka Cakung 01 - Yanto, Pingki Febri; Yulia, Elvyra; Atmanto, Dwi (Universitas Pahlawan Tuanku Tambusai, 2025)
Limited time and learning media for the topic of manual facial skin care at SMP Terbuka Cakung 01 have caused difficulties in the learning process. Based on the needs analysis, 100% of respondents agreed that the development of an interactive electronic module on manual oily skin facial care based on flipbook was necessary. The objective of this study is to develop an electronic module that serves as an informative and referential learning medium for students and the general public to enhance their skills in manual facial care for oily skin. This research employs a mixed-method approach, involving both quantitative and qualitative data collection and analysis. The study adopts a Research and Development (R&D) methodology using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), and is limited to the development phase. The development process includes validation by material and media experts, as well as practicality and effectiveness tests with students. Validation by Material Expert I showed an improvement from 85.71% in the first stage to 94.64% in the second stage. Validation by Material Expert II yielded a score of 96.42%, categorized as “Highly Feasible.” The media expert validation resulted in a score of 97.91%, also categorized as “Highly Feasible.” Practicality tests conducted with eighth-grade students at SMP Terbuka Cakung 01 showed results of 93.8% in the One-to-One trial and 90.19% in the Field Trial, both classified as “Highly Practical.” Effectiveness testing using the n-gain score method on seventh-grade students yielded an average pretest score of 0.41, a posttest score of 0.92, and an average n-gain score of 0.83, falling into the “High” category with an “Effective” interpretation. Therefore, the interactive electronic module on manual oily skin facial care based on flipbook can be considered an effective learning medium.